Leslie Wallace Lauste MBE (1908–2001): Brighton surgeon and prisoner of war in occupied Europe. (February 2022) - Taylor, Alexander William; Whiston, Benjamin; Cooper, Maxwell John
Leslie Wallace Lauste (1908–2001) was an English surgeon of French ancestry who practised in Brighton. This article used his memoirs and interviews to describe his life during the Second World War. In 1940, after declining evacuation by the Royal Navy, he was captured at Boulogne- Sur-Mer. Lauste went on to work in the following hospitals, of which most were attached to prisoner of war (POW) camps: Dannes-Camiers (France), Lille (France), Enghien (Belgium), Malines (Belgium), Dieberg (Germany), Klein-Zimmern (Germany), Stadtroda (Germany), Treysa (Germany), Kloster Haina (Germany), Lamsdorf (Poland), and Moosburg (Germany). Lauste's memoirs indicate that most surgical work was routine rather than trauma-related. He gained considerable freedoms in camp and attended external hospitals to give a surgical opinion. Lauste witnessed the consequences of allied bombing raids on German cities and considered these a "genocide." Lauste's life offers insight into the Nazi mistreatment of Russian prisoners, management of a typhus outbreak, camp liberation, and extraordinary journeys within occupied Europe. His memoirs provide new insight into the life of a British POW surgeon and reveals personal courage, kindness to others, and passion for medicine. Lauste never married. He died in Brighton in 2001.